Hugh Emlyn Davies. (5th November 2021) - Stephenson, Richard; Holland, Stuart
Abstract : An impeccably presented country gentleman, he was a skilled equine veterinary surgeon who combined excellent client service with a no‐nonsense approach and kept up to date with the latest developments.